HUBUNGAN PENGETAHUAN IBU TENTANG GIZI DENGAN STATUS GIZI ANAK USIA 3 – 5 TAHUN DI POSYANDU ANGGUR KECAMATAN SUMBERSARI KABUPATEN JEMBER - Harianah Akib; Zahruddin (Jurnal Kesehatan dr. Soebandi, 2016)
Nutritional status is a condition of balance between consumption and absorption of nutrients in the body. Nutritional status is important because one of the risk factors that cause death in children. Nutrition knowledge is one of the factors that influence children's food consumption. This study aims to analyze the Relationship between Mother's Knowledge of Nutrition and the Nutrition Status of Children 3 - 5 Years at Posyandu Wine Sumbersari, The design of this study is Cross Sectional. In this study there were 27 populations and a sample of 25 respondents with the technique of sampling using Simple Random Sampling. The results showed 60% of mothers had good knowledge and 76% of children had good nutritional status. from the results of the analysis test using the Spearman Rank of 95% (a = 0.05) pValue 0,000 <a (0.05). So in this study concluded, that the mother's knowledge about nutrition has a relationship with the nutritional status of children aged 3-5 years. This research suggests, whatever the level of education and occupation of the mother, the mother's knowledge of child nutrition problems needs to be improved to improve the nutritional status of children aged 3-5 years